Folding of guanine quadruplex molecules-funnel-like mechanism or kinetic partitioning? An overview from MD simulation studies - Šponer, Jiří; Bussi, Giovanni; Stadlbauer, Petr; Kührová, Petra; Banáš, Pavel; Islam, Barira; Haider, Shozeb; Neidle, Stephen; Otyepka, Michal (Biochimica et biophysica acta. General subjects, 2017)
BACKGROUND: Guanine quadruplexes (GQs) play vital roles in many cellular processes and are of much interest as drug targets. In contrast to the availability of many structural studies, there is still limited knowledge on GQ folding. SCOPE OF REVIEW: We review recent molecular dynamics (MD) simulation studies of the folding of GQs, with an emphasis paid to the human telomeric DNA GQ. We explain the basic principles and limitations of all types of MD methods used to study unfolding and folding in a way accessible to non-specialists. We discuss the potential role of G-hairpin, G-triplex and alternative GQ intermediates in the folding process. We argue that, in general, folding of GQs is fundamentally different from funneled folding of small fast-folding proteins, and can be best described by a kinetic partitioning (KP) mechanism. KP is a competition between at least two (but often many) well-separated and structurally different conformational ensembles. MAJOR CONCLUSIONS: The KP mechanism is the only plausible way to explain experiments reporting long time-scales of GQ folding and the existence of long-lived sub-states. A significant part of the natural partitioning of the free energy landscape of GQs comes from the ability of the GQ-forming sequences to populate a large number of syn-anti patterns in their G-tracts. The extreme complexity of the KP of GQs typically prevents an appropriate description of the folding landscape using just a few order parameters or collective variables. GENERAL SIGNIFICANCE: We reconcile available computational and experimental studies of GQ folding and formulate basic principles characterizing GQ folding landscapes. This article is part of a Special Issue entitled "G-quadruplex" Guest Editor: Dr. Concetta Giancola and Dr. Daniela Montesarchio.
Keywords: Nucleic Acid Denaturation; Base Pairing; lidé; vztahy mezi strukturou a aktivitou; G-kvadruplexy; simulace molekulární dynamiky; guanin; Kinetics; DNA; G-Quadruplexes; telomery; Humans; Guanine; kinetika; Molecular dynamics; G-quadruplex; Structure-Activity Relationship; Folding landscape; denaturace nukleových kyselin; Telomere; párování bází; Molecular Dynamics Simulation; Simulation force fields